Study guides

☆☆

Q: What is the simplification of the expression 3x plus 4y plus 2 plus 6y plus 3?

Write your answer...

Submit

Still have questions?

Related questions

It is: 3x+4y which is an algebraic expression

Collect like terms: 3x - x + 4x - 4y + 6y + 2 = 6x + 2y + 2

plot 4y then 3x

9x2 + 24xy + 16y2 = 9x2 + 12xy + 12xy + 16y2 = 3x(3x + 4y) + 4y(3x + 4y) = (3x + 4y)*(3x + 4y) = (3x + 4y)2

10x+4y+11xy

It's a linear expression in two unknowns.It can be simplified a little bit:18x + 14y + 3x - 10y = 21x + 4y

1

3x - 2y + 7x + 4y = 3x + 7x - 2y +4y = (3+7)x + (-2+4)y = 10x + 2y

(6x - 5y) + (-3x - 4y) =6x - 5y - 3x - 4y =3x - 9y =3 (x - 3y)

3x+4y+3 is ur answer, none of them are like terms so they can't be combineed

3x-3y

2x + 4y - 5x + 3y = 7y - 3x

People also asked